Can we rely on hybrid-DFT energies of solid-state problems with local-DFT geometries?. (1st February 2019) - Gouveia, J D; Coutinho, J
Abstract: Hybrid functionals often improve considerably the accuracy of density-functional calculations, in particular of quantities resulting from the band structure. In plane-wave (PW) calculations this benefit comes at the cost of an increase in computation time by several orders of magnitude. For this reason, large-scale problems addressed within the PW formalism have to rely on pre-relaxed atomistic geometries, obtained with cheaper local or semi-local exchange-correlation functionals. We investigate how suitable these geometries are when plugged into single-point hybrid-DFT calculations. Based on several case studies, we find two important sources of error originating from (i) bond strain and (ii) over-mixing between defect and crystalline states. The first arises from the mismatch between the pre-relaxed geometry and that obtained after a subsequent hybrid-DFT-level relaxation. The second occurs when defect states edging an underestimated band gap artificially mix with crystalline states, affecting the local bonding character of the defect, and therefore leading the spurious hybrid-DFT energies. Due to cancelation effects, the lingering strain contributes little ( 10 meV) to the error bar of quantities based on energy differences of pre-relaxed structures. The error from state over-mixing does not benefit from cancelation effects and has to be monitored with caution.